Stiffness modulation-driven wrinkle-free membrane - Ming Li; Yan Li; Chi Zhang; Guangliang Qi; Yu Sui; Yangjun Luo; Junshan Liu (Applications in Engineering Science, 2022)
Membranes are of rapidly increasing interest due to their lightweight and deployable properties. The key challenge in the development of membranes is eliminating wrinkles to avoid possible shape accuracy loss and related performance degradation in the high-velocity/resolution/frequency fields. In this paper, the stiffness modulation through spatioselective coating technique is adopted and the optimal distribution of coating materials is determined by a non-gradient topology optimization algorithm. The related wrinkle-free mechanism and performance are respectively investigated using numerical analysis and physical experiment. Our wrinkle-free approach, having lower fabrication complexity and compatible with mature additive manufacturing technique, offers a simple yet robust and scalable technique to achieve wrinkle-free membranes without any area loss.